2019
DOI: 10.1242/dev.173112
|View full text |Cite
|
Sign up to set email alerts
|

Barhl2 maintains T-cell factors as repressors, and thereby switches off the Wnt/β-Catenin response driving Spemann organizer formation

Abstract: A hallmark of Wnt/β-Catenin signaling is the extreme diversity of its transcriptional response, which varies depending on the cell and developmental context. What controls this diversity is poorly understood. In all cases, the switch from transcriptional repression to activation depends on a nuclear increase in β-Catenin, which detaches the transcription factor T cell factor 7 like 1 (Tcf7l1) bound to Groucho (Gro) transcriptional co-repressors from its DNA-binding sites and transiently converts Tcf7/Lymphoid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
27
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
3

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(31 citation statements)
references
References 89 publications
(134 reference statements)
4
27
0
Order By: Relevance
“…This interaction is independent of TCF7L1 binding to Gro/ TLE. Functional observations confirm that Barhl2 enhances the capacity of to repress transcription, and abolishes the β-catenin-driven activation of TCF/LEF target genes (Figure 1C) (Sena et al, 2019).…”
Section: Tcf/lef and Barhl2 In The Developmental Dynamics Of Spemann Organizer (So)supporting
confidence: 66%
“…This interaction is independent of TCF7L1 binding to Gro/ TLE. Functional observations confirm that Barhl2 enhances the capacity of to repress transcription, and abolishes the β-catenin-driven activation of TCF/LEF target genes (Figure 1C) (Sena et al, 2019).…”
Section: Tcf/lef and Barhl2 In The Developmental Dynamics Of Spemann Organizer (So)supporting
confidence: 66%
“…However, the regulation of competence for dorsal development appears to be context dependent and may involve additional factors, including alternative TCF proteins with distinct functions after the MBT (Hamilton et al, 2001) and pathway specific repressors such as BarH like homeobox 2 (Barhl2) (Sena et al, 2019) and Xcad2 (Levy et al, 2002) that appear to function downstream of Wnt-dependent activation of sia. Barhl2, which is expressed after the loss of competence to induce dorsal Wnt target genes, stabilizes the interaction of TCF3 (also known as TCF7l1) with Gro/TLE to repress of Wnt/ß-catenin target genes in a manner that depends on Hdac1.…”
Section: Discussionmentioning
confidence: 99%
“…Before stage 10, the transcription factor Barhl2 diminishes Spemann organizer fate determination 46 ; between stage 10 and stage 14, its overexpression promotes apoptosis in the Xenopus dorsal part. 16 We asked whether Barhl2 transcriptionally regulates mcl1.…”
Section: Depletion Of Barhl2 Activity Compensates For Mcl1 Depletion But Does Not Affect Apoptotic Cascade Components' Gene Expressionmentioning
confidence: 99%
“…We previously observed that Barhl2 overexpression promotes apoptosis in the Xenopus neuroectoderm, and mesoderm. 16,46 A phylogenetic analysis demonstrates that the nematode Ceh-30 is the ortholog of Barhl proteins (reviewed in References 81, 82. Three C. elegans genetic screens, performed independently, highlight the regulation of the apoptotic pathway by Barhl orthologs.…”
Section: Casp7 Is the Executioner Protease In Early Neurula Embryosmentioning
confidence: 99%